2022
DOI: 10.1186/s12954-022-00630-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying behaviours for survival and wellness among people who use methamphetamine with opioids in British Columbia: a qualitative study

Abstract: Background British Columbia (BC) has been in a state of public health emergency since 2016, due to the unprecedented numbers of fatal and non-fatal drug toxicity (i.e. overdose) events. Methamphetamine detection in illicit drug toxicity deaths increased from 14% in 2012 to 43% in 2020 suggesting a concerning trend of concurrent methamphetamine and opioid use in BC, consistent with rising patterns identified across North America. People who use methamphetamine concurrently with opioids face an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study consisted of semi-structured, one-on-one interviews conducted by phone or in-person as part of two qualitative studies performed across BC: the Concurrent Use and Transition to Methamphetamine among People at Risk of Overdose (CUT Meth OD) study (n = 27) and the Good Samaritan Drug Overdose Act (GSDOA) evaluation study (n = 35) [28,29]. Qualitative interview guides were developed by the research team -including researchers, people with lived and living experience of substance use, stakeholders from community organizations, health authorities, and young adults.…”
Section: Methodsmentioning
confidence: 99%
“…This study consisted of semi-structured, one-on-one interviews conducted by phone or in-person as part of two qualitative studies performed across BC: the Concurrent Use and Transition to Methamphetamine among People at Risk of Overdose (CUT Meth OD) study (n = 27) and the Good Samaritan Drug Overdose Act (GSDOA) evaluation study (n = 35) [28,29]. Qualitative interview guides were developed by the research team -including researchers, people with lived and living experience of substance use, stakeholders from community organizations, health authorities, and young adults.…”
Section: Methodsmentioning
confidence: 99%
“…We found that more than 60% of the sample reported the use of both opioids and stimulants, re ecting high rates of co-use of these substances, which have been reported more widely in population-level samples in BC, Canada, and North America(29-33). People are known to have a range of motivations for co-use (34) and to practice strategies to protect from harm (35), nevertheless the risk of harm persists given the rising toxicity of the unregulated drug supply in BC (36). Despite this co-use being common, only 30% of people who received an opioid PSS prescription in this study also received a stimulant PSS prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent reporting on illicit drug toxicity deaths in BC found that many people who died had not been previously engaged in SUD treatment, suggesting that the risk of overdose in BC extends beyond people with diagnosed SUDs. 50 As such, cases of death in people with neither diagnosis could represent people who use drugs irregularly, and who do not have the same tolerance nor knowledge and skills 51 , 52 to prevent or reduce overdose risk as people with more experience using drugs, including people with SUDs. Furthermore, some interventions meant to prevent overdose are available in BC for people with OUD that are not available to people without an OUD diagnosis.…”
Section: Discussionmentioning
confidence: 99%